Time-dependent POVM reconstruction for single-photon avalanche photo diodes using adaptive regularization. (1st February 2022) - Fitzke, E; Krebs, R; Haase, Th; Mengler, M; Alber, G; Walther, Th
Abstract: We report on the first realization of time-dependent quantum detector tomography for commercially available InGaAs avalanche photo detectors. For the construction of appropriate time-dependent POVMs from experimentally measured data, we introduce a novel scheme to calculate the weight of the regularization term based on the amount of measured data. We compare our POVM-based results with the theoretical predictions of the previously developed model by Gouzien et al (2018 Phys. Rev. A 98 013833). In contrast to our measurement-based construction of a time-dependent POVM for photon detectors, this previous investigation extends a time-independent POVM to a time-dependent one by including effects of detector timing jitter and dead time on the basis of particular model assumptions concerning the inner physical mechanisms of a photon detector. Our experimental results demonstrate that this latter approach is not sufficient to completely describe the observable properties of our InGaAs avalanche photo detectors. Thus, constructing the time-dependent POVM of a detector by direct quantum tomographic measurements can reveal information about the detector's interior that may not easily be included in time-independent POVMs by a priori model assumptions.